Título Padrão: um estudo de acessibilidade - de Almeida Costa, Ana Cristina; Chalhub, Tania (Informação em Pauta, 2023)
Technologies in recent decades have impacted all spheres of society. For people with disabilities, it has enabled the existence of resources that improve their quality of life, such as architectural, attitudinal and informational accessibility. In this research the focus will be on informational accessibility in school libraries where, despite technological advances, resources for users with disabilities are still embryonic. The objective of this work is to discuss the types of accessible materials and resources of Assistive Technologies present in the library of the School of Application of the Federal University of Pará (EAUFPA- a lab school aimed to provide training field and research for students of the University´s College of Education). This is a case study, with a quantitative and qualitative approach with content analysis. According to the research results, the library in question has some accessible materials for deaf and blind people, however, it still needs to advance in materials for audiences with other disabilities such as cognitive impairment. Regarding Assistive Technologies, there is the presence of screen reader software, but it still has gaps for other resources such as magnifiers. One of the contributions of this study is the disclosure of the information accessibility scenario in a public school library that uses technologies, mostly open access, expanding the visibility of these resources and their use in other school libraries.